Pier Paolo Vergerio e Coluccio Salutati - Solymosi, Milán (Verbum – Analecta Neolatina, 2002)
In this article we have an overview of the life and activity of Pier Paolo Vergerio, an Italian humanist who lived for 26 years in Hungary, at the court of Sigismund of Luxemburg. The Author shows the relations of Vergerio with contemporary other Italian humanists, specially Coluccio Salutati and indicates possible connections with the second generation of Humanism in Hungary.